Developing Taking Perspective Skills of Children Aged 5-8 Years Through Story Book Reading - Choiriyah Widyasari; Siti Zuhriah Ariatmi; Almuntaqo Zainuddin (Department of Early childhood Education, 2018)
Perspective taking is used by a child to understand the feelings or conditions of others and show affective response that is similar to what is felt by others. Children aged 5-8 are in the peak of developing their ability to recognize and understand others. As an attempt to develop such ability, teachers can perform the activities of picture story book reading that contain moral values to students. The present study aims to find out the differences in children’s perspective-taking skills before and after the activity of story book reading.The research used experimental design. The subjects were the students of TK Al Islam 1 Surakarta. The instrument used in this study was developed by the researchers. Prior to its implementation, construct validation was done resulted to the value of Content Validity Index (CVI) = 1.00. It showed that the instrument had good value and fulfilled the expected elements.The findings show the difference in the perspective-taking skills of children aged 5-8 years as indicated by the results of the pre- and post-experiment, with the mean X.1 = 21.75 X.0 = 19.28. It implies that the activity of story book reading is effective in enhancing the perspective-taking skills of a child.